PENGARUH PENGGUNAAN MODEL BLENDED LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR KELAS V SD NEGERI 13 TOBOALI - Sendi Aprilia; Jaka Permana; Darda Abdullah Sjam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Choosing a good learning model during the Covid-19 pandemic can help and make it easier for teachers to deliver learning material to students. a learning model that can be applied according to the characteristics of students is a blended learning model. The purpose of this study was to determine the concept of the Blended Learning Model to Increase the Learning Motivation of Elementary School V Students at SD Negeri 13 Toboali. This study uses a quantitative approach with a research design that is quasi-experimental. The sampling technique used in this study was purposive sampling. The sample of this study was students of class V at SD Negeri 13 Toboali, so class V-A (experimental) and class V-B (control) were taken as a sample of 15 students each. then the total of the experimental class and the control class is 30 students. The data collection technique used in this study was a questionnaire. The results showed that the data analysis using a simple linear regression test obtained t-count of -1.592 with a sig value of 0.135 > 0.05. It can be concluded that blended learning has a negative and insignificant effect on students' learning motivation in class V SDN 13 Toboali. Using the paired sample t test, it shows that the control class has an average value of 57.93 with an error of 1.5. Meanwhile, the experimental class had a higher average value than the control class, which was 61.13 with an error of 1.6. It can be concluded that there was no significant difference in the results obtained before and after applying blended learning to fifth grade students at SDN 13 Toboali.